ANALISIS MODEL BISNIS PADA KEDAI KOPI BARIKA PEMATANGSIANTAR DENGAN PENDEKATAN BUSINESS MODAL CANVAS - Reza Afriza; Risma Nurhaini Munte; Liharman Saragih; Yoan Hendrawan Saragih (Jurakunman (Jurnal Akuntansi dan Manajemen), 2022)
The purpose of this research is to develop the Kedai Kopi Barika business using the Business Modal Canvas.  The business model canvas is a hypothesis about a company that wants to make a profit.  In this study, the researcher tried to identify how the canvas business model was applied to Kedai Kopi Barika by using primary data types with the interviewee method.  This study also aims to map business processes using nine business model canvas blocks to solve existing problems.  The result is how the application of the canvas business model affects the growth of Kedai Kopi Barika. Keywords: Business Modal Canvas; Business Modal; 9 Blok Of Business Modal